On the effect of business and economic university education on political ideology: An empirical note - Manthos D. Delis; Iftekhar Hasan; Maria Iosifidi (Bank of Finland, 2017)
We empirically test the hypothesis that a major in economics, management, business administration or accounting (for simplicity referred to as business/economics) leads to more-conservative (right-wing) political views. We use a panel dataset of individuals (repeated observations for the same individuals over time) living in the Netherlands, drawing data from the Longitudinal Internet Studies for the Social Sciences from 2008 through 2013. Our results show that when using a simple fixed effects model, which fully controls for individuals' time-invariant traits, any statistically and quantitatively significant effect of a major in business/economics on the political ideology of these individuals disappears. We posit that, at least in our sample, there is no evidence for a causal effect of a major in business/economics on individuals' political ideology.
URN:NBN:fi:bof-201708111506
Keywords: I21; M2; D72; 330